Association of screen time with long-term stress and temperament in preschoolers: results from the DAGIS study - Leppänen M; Sääksjärvi K; Vepsäläinen H; Ray C; Hiltunen P; Koivusilta L; Erkkola M; Sajaniemi N; Roos E (Springer, 2022)
Screen time is increasing rapidly in young children. The aim of this study was to examine associations of long-term stress and temperament with screen time in Finnish preschool children and the moderating role of socioeconomic status. Cross-sectional DAGIS data were utilized. Long-term stress was assessed using hair cortisol concentration, indicating values of the past 2 months. Temperament was reported by the parents using the Children’s Behavior Questionnaire (the Very Short Form), and three broad temperament dimensions were constructed: surgency, negative affectivity, and effortful control. Screen time was reported by the parents over 7 days. The highest education level in the household was used as an indicator of socioeconomic status. In total, 779 children (mean age, 4.7 ± 0.9 years, 52% boys) were included in the study. Of the temperament dimensions, a higher effortful control was associated with less screen time (B = − 6.70, p = 0.002). There was no evidence for an association between hair cortisol concentration and screen time nor a moderating role of socioeconomic status in the associations (p > 0.05).
Conclusion: Our findings indicate that preschool children with a higher score in effortful control had less screen time. Because effortful control reflects general self-regulatory abilities, promoting these skills may be effective in reducing screen time in young children.